Studying foreign experience in the development of a business system - Kadamboyev Behzod Shuxrat o’g’li; Sa’dullayeva Zilola Davronbek qizi (Global Scientific Publishing, 2022)
Global digitization has a dramatic impact on the tourism industry, radically renewing the principles of its organization, providing tourism and the traveler himself with information. The article analyzes foreign scientific research on the problem of introducing digital technologies for the development of tourism and other similar fields.
Keywords: Tourism; infrastructure; market; business